Feasibility of a novel classification for parotid gland cytology: A retrospective review of 512 cytology reports taken from 4 United Kingdom general hospitals. Issue 11 (21st April 2016) - Bajwa, Mandeep S.; Rose, Samantha J.; Mairembam, Priya; Nash, Robert; Hotchen, David; Godden, Daryl; Alam, Peyman; Daborn, Louise; Spedding, Anne V.; Brennan, Peter A.
Abstract: Background: A novel classification for parotid cytology has been previously proposed. The purpose of this study was to assess the feasibility and clinical relevance of this classification. Method: Between 2010 and 2013, cytology reports from 4 United Kingdom general hospitals were retrospectively classified and compared to histological and clinical outcomes. Results: Based on the cytology reports of 512 patients, we revised our previous "P" system to a "Sal" (salivary) classification to encompass all cytologic outcomes. The percentage of patients with a final diagnosis of malignancy according to each category heading were: Sal 1 (inadequate) 7.9%; Sal 2I (nonneoplastic) 10%; Sal 2N (benign neoplastic) 1.4%; Sal 3 (atypical) 20.4%; Sal 4 (suspicious) 52.6%; Sal 5P (primary salivary gland malignancy) 71.4%; Sal 5NOS (malignancy not otherwise specified) 100%; and Sal 5M (metastasis) 91.7%. Conclusion: By stratifying the probability of encountering a malignant neoplasm, the classification could guide clinical management decisions. A future prospective study is warranted. © 2016 Wiley Periodicals, Inc. Head Neck 38 : 1708–1716, 2016